Digitalization as a Strategy to Increase the Competitiveness of MSMEs in the Era of an Inclusive Economy - Agusman, Agusman; Victor, Victor (Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to investigate the main strategies in increasing the competitiveness and sustainability of micro, small, and medium enterprises (MSMEs) in the tourism sector in Medan City through digitalization and technological innovation in the framework of an inclusive economy. The focus of the research includes the use of digital technology in marketing, optimization of online reservation systems, the use of e-commerce platforms, and the application of service automation to increase operational efficiency and MSME revenue. Digitalization is seen as a strategic solution to overcome MSMEs' dependence on conventional methods in marketing, production, and business management which has been the main obstacle in facing competition with large companies and imported products. Based on data from the Medan City Cooperative Office, there are around 18,000 active MSMEs, but the level of digital adoption still varies. This study uses a quantitative method with purposive sampling techniques on 100 MSMEs from the souvenir, culinary, and handicraft subsectors that have interacted with local digitalization programs. Data were collected through a questionnaire survey and analyzed using Structural Equation Modeling with a Partial Least Squares (PLS-SEM) approach because the research variables were latent and construct-based. This approach allows testing of structural relationships as well as direct and indirect influences between variables. The novelty of this research lies in the development of the Conceptual Model of Inclusive Digitalization for SME Competitiveness (CDISC), which integrates digital inclusivity indicators—including digital access, digital literacy, and technological readiness—with MSME competitiveness indicators. The results of the research are expected to make a theoretical and practical contribution to the development of MSME digitalization policies that are sustainable, inclusive, and oriented towards increasing turnover, expanding market reach, and operational efficiency of MSMEs in Medan City